Generalized difference sequences of fuzzy numbers - Colak, Rifat; Altinok, Hifsi; Et, Mikail (Pergamon-Elsevier Science Ltd, 2009)
The idea of difference sequences of real (or complex) numbers was generalized by Et and Colak [Et M, Colak R. On some generalized difference sequence spaces. Soochow J Math 1995; 21(4): 377-86; Colak R, Et M. On some generalized difference sequence spaces and related matrix transformations. Hokkaido Math J 1997; 26(3): 483-92]. In this paper, using the difference operator Delta(m) and an Orlicz function, we introduce and examine some sequence spaces of fuzzy numbers. We study some of their properties like completeness, solidity, symmetricity, etc. We also give some relations related to these spaces. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: E-Infinity Theory; Spaces; Convergence; Spectrum; Delta; Sets